Use for newer Imaging Modalities for Airway Management - Rakesh Garg; Namita Saraswat (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2015)
Airway management has made many advances in recent years. However, an unanticipated difficult airway can turn out to be a nightmare for anaesthesiologist. The various predictors include clinical assessment predictors, X-ray neck, conventional helical computed tomographic (CT) scan, indirect laryngoscopy, pulmonary function tests and fiberoptic bronchoscopy had been successfully used for delineation of airway anatomy [1]. The shortcomings of aforementioned techniques except for fiberoptic bronchoscopy are that they tell about static component without giving much information about dynamic component of airway. Fiberoptic bronchoscopy is invasive and could not be performed without prior anaesthetic preparation. However newer modalities like ultrasonography, multidetector CT (MDCT) scan with virtual 3D  bronchoscopic image (VB) reconstruction are upcoming imaging modality which provides both static and dynamic or virtual airway information. Precisely they allow non-invasive intraluminal as well as extraluminal evaluation of the airway.